Non-contact child sexual abuse: Characteristics in a representative Spanish sample - Ferragut-Ortiz-Tallo, Marta; Ortiz-Tallo-Alarcón, Margarita; Blanca-Mena, María José (Sage, 2025)
There is growing interest in understanding non-contact violence in the context of child sexual abuse (CSA). This study explores the characteristics of four types of non-contact CSA in a representative sample of the Spanish population. A sample of 1,071 Spanish adults (53% males; mean age 45.37 years) completed the Child Sexual Abuse Experiences Questionnaire. For each type of non-contact CSA experience, we analyzed the victim’s age at the time of the first incident, the frequency of occurrence, whether the perpetrator was the same individual (if multiple occurrences), the perpetrator’s gender, and the victim’s relationship to the perpetrator. Victim gender differences were examined for all variables. Some form of non-contact abuse had been experienced by 34.50% of the sample. Victims were most commonly aged between 12 and 15 years at the time of the first incident (37.6%), followed by ages 6–11 (31.7%). Over half of the victims (especially females) experienced abuse repeatedly. A significant proportion of those surveyed (55.7%) had been abused by different individuals, mainly males, although the percentage reporting a female perpetrator was higher among male victims. Perpetrators were most commonly an adult stranger or acquaintance, with gender differences emerging in cases where the perpetrator was another minor or someone in a position of responsibility, two scenarios that were more commonly reported by male victims. Non-contact CSA is becoming increasingly common in our connected society and shows specific characteristics that may differ across gender. These characteristics and differences are discussed in this research.
https://openpolicyfinder.jisc.ac.uk/id/publication/22301
Keywords: Niños víctimas de abusos sexuales; Delitos sexuales; Child sexual abuse; Non-contact abuse; Sexual aggression; Victims; Perpetrator